reviewws2_math116

reviewws2_math116 - y = [(x+3) * 9 + (x 5)] / [(x+3)(x-5)]...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
106 great job Math 116 Kim Peppard instructor – online -5 wrong file name 1. a. y’= (5x^6 -3x^4 +25x^3 -1)(4x -8) + (2x^2 -8x +9)(30x^5 -12x^3 +75x^2) b. outside = -15( )^-`6 inside = (10x^4 -15x^2 +1) y`= -15(2x^5 -5x^3 +x -2)^-16(10x^4 -15x^2 +1) c. y’ = (2x^2)*1/2(9-x)^-1/2 + (4x)*(9-x)^1/2 y’= (2x^2)/2(9-x)^1/2 + (4x)(9-x)^1/2 y’ = x^2/[(9-x)^1/2 + (4x)(9-x)^1/2] negative on first term d. –1 e. f. y’ = [(5x^3 +2x)^5 * 3 – (3x-1)*5(5x^3+2x)^4(15x^2+2)] /(5x^3+2x)^10 y’ = [(5x^3 +2x) * 3 – (3x-1) * 5(15x^2+2)] / (5x^3+2x)^6 2. a. outside’ = 1/(3x^4 –2x) inside ‘ = 12x^3 –2 y’ = (12x^3 –2)/(3x^4 –2x) b. y’ = [(3x – 7)/(5x^3 +2)] [(5x^3 + 2)*3 – (3x-7)*15x^2]/ (3x-7)^2 y’ = [(5x^3 + 2) * 3 – (3x – 7) * 15x^2] / [(5x^3 + 2)(3x – 7)] c. y’ = 1 / [(x+3)(x-5)^9] * {[(x+3) * 9(x-5)^8 + (x-5)^9] / [(x+3)(x-5)^9]} y’ = [(x+3) * 9(x-5)^8 + (x-5)^9] / [(x+3)(x-5)^9] / [(x+3)(x-5)^9]
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: y = [(x+3) * 9 + (x 5)] / [(x+3)(x-5)] y = (10x + 22) / [(x+3)(x+5)] 3. a. y = -18e^x * 1 y = -18e^x b. y = e^(3x^2 5x) * (6x 5) c. y = (x^8)(e^-2x * -2) + (8x^7)(e^-2x) y = (e^-2x * x^7)(-2x + 8) y = (-2x^7 * e^-2x)(x 4) 4. a. 10x^4 3y^2(y) + 3y = 0 3y 3y^2(y) = -10x^4 y = -10x^4 / (3 3y^2) y = (-10x^4 3y)/(-3y^2 + 3x)-7 5. a. 90x^9 32x^7 42x^5 810x^8 224x^6 210x^4 y = 6480x^7 1344x^5 840x^3 +6 b. (e^(5x^6) * 150x^4) + (e^(5x^6) * 30x^5 * 30x^5) e^(5x^6) * (150x^4 + 900x^10) 150x^4 * e^(5x^6)*(1 + 6x^6) +6 c. y = (x^7)(1/x) + (7x^6)(ln x) y = 6x^5 + 42x^(ln x) + (1/x)(7x^6) y = 6x^5 + 42x^(ln x) + 7x^5 y = 13x^5 + 42x^5(ln x) +6...
View Full Document

Page1 / 2

reviewws2_math116 - y = [(x+3) * 9 + (x 5)] / [(x+3)(x-5)]...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online